Transformation Towards Self-Built Architecture (Journal of University of Babylon for Engineering Sciences, 2019)
The concept of transformation has been invested in architecture using bio-simulation as a means to produce architecture that responds to different influences. In a similar way, the building transforms the behavior of living organisms in its adaptation to environmental influences during the construction of its structure. The need to clarify the concept and approach to the transition towards self-construction architecture, which expresses the goal of research in building a theoretical framework to study the research problem and extracted from the various design and implementation methods in architectural projects and to reach a number of key and secondary vocabulary and applied to selected projects and conduct measurement. Using mechanics of growth and manufacturing using advanced digital materials is the future orientation ofarchitecture to be self-construct.